GCMAC-based predistortion for digital modulations. - Gonzalez-Serrano, F.-J (IEEE Transactions on communications)
The subject of this paper is the compensation for nonlinearities in digital communication systems by means of predistortion. In this work, we apply the generalized cerebellar model articulation controller (GCMAC) to simplify and accelerate the predistorter convergence. The range of analyzed predistorters includes: 1) a symbol-rate data predistorter that, for a given time span, achieves a similar level of compensation provided by present techniques, but with faster convergence; 2) a fractionally spaced data predistorter that controls, at the same time, the signal constellation and the transmitted spectrum; 3) a decision-feedback scheme that compensates for remote nonlinearities; and 4) a digital signal data predistorter. The performance of the proposed data and signal predistorters is evaluated using typical linear and nonlinear modulated transmitted signals such as QAM and GMSK